Relative age effects in professional German soccer: A historical analysis - Cobley, S. P.; Schorer, J.; Baker, J. (Journal of Sports Sciences, 2008)
Relative age effects (RAEs) refer to the specific selection, participation and attainment (dis)advantages which occur as a result of physical and cognitive differences within annual age-grouped cohorts. The present study tracked the existence of RAEs in professional German soccer by examining RAEs in players, head coaches and referees who represented professional soccer clubs or officiated in the Bundesliga from 1963/64 to 2006/07. An additional objective was to consider the social-cultural mechanisms responsible for RAEs, so for a similar period, population and soccer participation information was also obtained. When players were categorised into half decade groups, chi-square analyses predominantly showed RAEs across the history of the Bundesliga, irrespective of dates used for annual age grouping in junior/youth soccer. RAEs were also apparent for head coaches but not for referees. Participation data indicated consistent and progressive growth from 1950 to 1990. RAEs influence the likelihood of attaining professional player and coaching status in German soccer. With many coaches being former players, inequalities associated with annual age-grouping appear to extend beyond a playing career. Officiating was not affected, with referees suggested to emerge from an alternative development pathway. Increased popularity of soccer may have propagated RAEs over time, through intensification of competition and selection mechanisms.